Idiopathic Gingival Fibromatosis: Case Report and Its Management - Prashant P. Jaju; Ankit Desai; Rajiv S. Desai; Sushma P. Jaju (International Journal of Dentistry)
Idiopathic gingival fibromatosis is a rare condition. We present a case of idiopathic gingival fibromatosis with its multidisciplinary approach of management. The clinical, radiographic, and histopathological features have been described in detail.